2014
DOI: 10.1101/008482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual dimorphism in epigenomic responses of stem cells to extreme fetal growth

Abstract: Extreme fetal growth is associated with increased susceptibility to a range of adult diseases through an unknown mechanism of cellular memory. We tested whether heritable epigenetic processes in longlived CD34+ hematopoietic stem/progenitor cells (HSPCs) showed evidence for re-programming associated with the extremes of fetal growth. Here we show that both fetal growth restriction and overgrowth are associated with global shifts towards DNA hypermethylation, targeting cis-regulatory

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…Interestingly, a sexual dimorphic effect was observed in which the number of hypermethylated loci was markedly higher in IUGR male infants and LGA female infants [10]. Furthermore, methylation differences were found in genes belonging to pathways for MODY and hedgehog (HH) signalling, both of which are associated with premature glucose intolerance, type 2 diabetes and stem cell proliferation/ renewal [10]. These studies highlight the potential role of dysregulated DNA methylation in key metabolic pathways in metabolic disease susceptibility.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Interestingly, a sexual dimorphic effect was observed in which the number of hypermethylated loci was markedly higher in IUGR male infants and LGA female infants [10]. Furthermore, methylation differences were found in genes belonging to pathways for MODY and hedgehog (HH) signalling, both of which are associated with premature glucose intolerance, type 2 diabetes and stem cell proliferation/ renewal [10]. These studies highlight the potential role of dysregulated DNA methylation in key metabolic pathways in metabolic disease susceptibility.…”
Section: Introductionmentioning
confidence: 87%
“…Other studies have shown distinct methylation patterns in haematopoietic CD34 + stem cells purified from cord blood of infants exposed to IUGR (referred to as 'IUGR infants') as well as those who were large for gestational age (LGA), when compared with infants who were appropriate for gestational age (AGA). Interestingly, a sexual dimorphic effect was observed in which the number of hypermethylated loci was markedly higher in IUGR male infants and LGA female infants [10]. Furthermore, methylation differences were found in genes belonging to pathways for MODY and hedgehog (HH) signalling, both of which are associated with premature glucose intolerance, type 2 diabetes and stem cell proliferation/ renewal [10].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations